(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The progressive socio-economic development of society in all areas urgently requires the active inclusion of the intellectual, creative potential of almost every person in the social circulation. This setting is especially relevant for education, the most important task of which is to provide everyone with the opportunity to fully reveal their inclinations and develop the ability to be creative. Creativity is a socio-historical phenomenon of human self-development in the process of material and spiritual exploration of the world. Creative activity is realized in various spheres of society, which is why there are various types of it, including pedagogical creativity. In this article described issues based on organizational and pedagogical conditions for the creative activity of the future teacher